2010
DOI: 10.1175/2009jcli3240.1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Tropical Deep Convection with the Large-Scale Circulation in the MJO

Abstract: To better understand the interaction between tropical deep convection and the Madden–Julian oscillation (MJO), tropical cloud regimes are defined by cluster analysis of International Satellite Cloud Climatology Project (ISCCP) cloud-top pressure—optical thickness joint distributions from the D1 dataset covering 21.5 yr. An MJO index based solely on upper-level wind anomalies is used to study variations of the tropical cloud regimes. The MJO index shows that MJO events are present almost all the time; instead o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…8d). This radar-based finding well matches the satellitebased finding that deep narrow (or isolated) convection is more prevalent during preonset MJO periods, while wide (or organized) convection is more common during active periods (Morita et al 2006;Tromeur and Rossow 2010;Riley et al 2011). Though the deep convective population decreases more than 40% when the active phase evolves to phase 3 (Fig.…”
Section: B Precipitating-cloud Populationsupporting
confidence: 86%
See 1 more Smart Citation
“…8d). This radar-based finding well matches the satellitebased finding that deep narrow (or isolated) convection is more prevalent during preonset MJO periods, while wide (or organized) convection is more common during active periods (Morita et al 2006;Tromeur and Rossow 2010;Riley et al 2011). Though the deep convective population decreases more than 40% when the active phase evolves to phase 3 (Fig.…”
Section: B Precipitating-cloud Populationsupporting
confidence: 86%
“…More recent studies have investigated the MJO cloud population, precipitation structure, dynamical structure, and the interaction of convection with the large-scale environment using radiosonde or satellite sounding data (Kiladis et al 2005;Tian et al 2006), model reanalysis (e.g., Kiladis et al 2005;Benedict and Randall 2007), satellite precipitation retrievals (Tian et al 2006;Morita et al 2006;Benedict and Randall 2007), and satellite cloud measurements (Tromeur and Rossow 2010;Lau and Wu 2010;Virts et al 2010;Riley et al 2011;Del Genio et al 2012;Barnes and Houze 2013). These results showed that cloud systems across the MJO cycle basically progress from shallow cumulus, to cumulus congestus, to deep convection, and finally stratiform.…”
Section: Introductionmentioning
confidence: 97%
“…Despite plausible features in these results, T B measurements are known to suffer from cirrus contamination (low T B may not always correspond to deep convective clouds, rather the satellite could be seeing a cold, nonprecipitating high cirrus cloud). Tromeur and Rossow (2010) show that OLR does not distinguish between the different kinds of convection that are identified by the ISCCP WS in the tropics. Tromeur and Rossow (2010) show that OLR does not distinguish between the different kinds of convection that are identified by the ISCCP WS in the tropics.…”
Section: Deep Convection and Aew Initiation Over East Africamentioning
confidence: 73%
“…These exchanges drive global weather systems on scales ranging from individual thunderstorms to global circulation patterns [1][2][3][4], including polar lows containing hurricane-force winds exceeding 25 m s −1 [5]. Representing a primary conduit for atmosphere-ocean communication, air-sea interactions serve as the linchpin connecting the Earth's ocean and atmosphere [6,7].…”
Section: Introductionmentioning
confidence: 99%